2003
DOI: 10.1063/1.1568118
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic effects on the stability properties of field-reversed configurations. I. Linear stability

Abstract: New computational results are presented which advance the understanding of the stability properties of the Field-Reversed Configuration (FRC). We present results of hybrid and two-fluid (Hall-MHD) simulations of prolate FRCs. The n = 1 tilt instability mechanism and growth rate reduction mechanisms are investigated in detail including resonant particle effects, finite Larmor radius and Hall stabilization, and profile effects. It is shown that the Hall effect determines the mode rotation and the change in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…This generic idea has been verified in C-2 experiment carried out recently at Tri Alpha Energy Company [30]. Although promising FRC reactor concepts have been developed in the past [4], a reactor design is outside the scope of the present paper, The physics basis for the SPIRIT concept has been verified in numerical calculations [6][7][8][9][10][11][12][13], as well as oblate FRC experiments. Some numerical studies have found an operation regime in an oblate FRC which is stable against all global modes.…”
Section: Spirit Conceptmentioning
confidence: 79%
See 3 more Smart Citations
“…This generic idea has been verified in C-2 experiment carried out recently at Tri Alpha Energy Company [30]. Although promising FRC reactor concepts have been developed in the past [4], a reactor design is outside the scope of the present paper, The physics basis for the SPIRIT concept has been verified in numerical calculations [6][7][8][9][10][11][12][13], as well as oblate FRC experiments. Some numerical studies have found an operation regime in an oblate FRC which is stable against all global modes.…”
Section: Spirit Conceptmentioning
confidence: 79%
“…In these studies, (a) the role of ion FLR effects in affecting FRC stability properties has been clarified showing stability of FRC for finite gyro-radius effects; (b) resonant particle effects have been demonstrated to be responsible for the instability drive in cases where FLR effects and the Hall term stabilize the MHD-unstable modes [10]; (c) modern relaxation theory and the properties of two-fluid flowing equilibria have been studied; (d) and the nonlinear saturation of the n=1 tilt instability has been discovered in low-S* configurations [11]. The recent simulations demonstrate for variety of equilibria that the normalized tilt mode growth rate is a function only of the parameter S*/E [8]. This supports the empirical stability scaling obtained earlier with the parameter S*/E [5] shown in Eq.…”
Section: The Stability Of Frcs and The Effects Of Finite Ion Gyro-radiusmentioning
confidence: 99%
See 2 more Smart Citations
“…Simulations using both the gyroviscous formulation 40 and with a hybrid code 41 have predicted that FLR effects cannot reduce the tilt mode linear growth rate to zero in a prolate FRC. However, the nonlinear saturation of the tilt instability was observed in hybrid simulations, 42 as the plasma nonlinearly evolved to a new rotating equilibrium from a stationary initial condition.…”
Section: ͑3͒mentioning
confidence: 99%